2021
DOI: 10.1186/s12966-021-01157-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of daily composition of physical activity and sedentary behaviour with incidence of cardiovascular disease in older adults

Abstract: Background Moderate-to-vigorous physical activity (MVPA) is proposed as key for cardiovascular diseases (CVD) prevention. At older ages, the role of sedentary behaviour (SB) and light intensity physical activity (LIPA) remains unclear. Evidence so far is based on studies examining movement behaviours as independent entities ignoring their co-dependency. This study examines the association between daily composition of objectively-assessed movement behaviours (MVPA, LIPA, SB) and incident CVD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 56 publications
2
17
0
1
Order By: Relevance
“…In contrast using objectively assessed SB, the Objective Physical Activity and Cardiovascular Health (OPACH) study of older women found a linear dose–response relationship where each 1 additional hour of sedentary time was associated with 12% higher CVD risk ( 18 ) in model accounting for multiple risk factors and MVPA. In other studies the associations were attenuated on adjustment with higher intensity PA ( 17 ), health-related factors ( 41 , 42 ), or both ( 40 ), as also found in our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast using objectively assessed SB, the Objective Physical Activity and Cardiovascular Health (OPACH) study of older women found a linear dose–response relationship where each 1 additional hour of sedentary time was associated with 12% higher CVD risk ( 18 ) in model accounting for multiple risk factors and MVPA. In other studies the associations were attenuated on adjustment with higher intensity PA ( 17 ), health-related factors ( 41 , 42 ), or both ( 40 ), as also found in our study.…”
Section: Discussionsupporting
confidence: 90%
“…11,12 In this study we examined associations of multiple sedentary accumulation pattern measures with both outcomes, given that different metrics might be indicative of distinct features of SB. Based on our findings, we reiterate the importance of MVPA for CVD prevention, 42 as associations of total sedentary time and accumulation patterns with CVD risk were no more evident once MVPA was considered. In addition, there was evidence of higher all-cause mortality risk with increased total and less fragmented sedentary time independently from MVPA in the younger older adults.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…51 A recent study demonstrated that an increase in moderate-intensity PA would reduce the incidence of CVD. 52 Present study findings demonstrate that insufficient PA contributed to a greater 10year CVD risk in Indians. Evidence suggests that sufficient levels of PA reduce the possible risk of development of NCDs.…”
Section: Discussionsupporting
confidence: 51%
“…One of the risk factors most alarmingly associated with work is sedentary lifestyle because most jobs have a fixed schedule associated with a specific location. With advanced age, this tendency towards sedentary habits increases, particularly when associated with the time each individual spends sitting per day [ 65 , 66 , 67 ]. In this study, we deal with an aging work population (70.7% are aged between 45 and 64 years).…”
Section: Discussionmentioning
confidence: 99%